PENAMPILAN PRODUKSI KELINCI PERIODE PERTUMBUHAN YANG DIBERI PAKAN WAFER LIMBAH DAUN UBI JALAR (IPOMEA BATATAS) DENGAN PENAMBAHAN BERBAGAI LEVEL MOLASES - Anwar Efendi Harahap; E Saleh; N Nurjannah (Jurnal Peternakan, 2019)
The aim of this research is to determine of the wafer of performance of rabbits in the growth period given wafer sweet potato leaves waste with various levels of molasses.  In The result showed that the treatment in this experiment had no significant effect (P>0.05) on feed consumption, average daily gain, feed conversion. The conclusion of this experiment is that giving molasses to complete ration wafers up to the level of 15 % in the rabbit unable to increase feed consumption (g/head/day), body weight (g/head/day) and  feed conversion